THE RELATIONSHIP BETWEEN FAT INTAKE AND LDL CHOLESTEROL LEVELS IN OUTPATIENTS WITH CORONARY HEART DISEASE AT DR. PIRNGADI GENERAL HOSPITAL, MEDAN - Simamora, Cike Grenada Sriningsih; Rukmana, Erni; Emilia, Esi; Purba, Edy Marjuang; Sandy, Yatty Destani (Jurnal Gizi dan Pangan Soedirman, 2025)
Coronary heart disease (CHD) begins with blockage of blood vessels due to plaque buildup in the heart, which occurs when there is an excess of LDL cholesterol, causing damage to the blood vessels. Based on provincial data, the prevalence of heart disease in North Sumatra is 0.60% or around 48,469 cases. One of the causes of coronary heart disease is high fat intake and high LDL cholesterol levels. This study aims to identify the relationship between fat intake and LDL cholesterol levels in outpatients with coronary heart disease at the cardiology clinic of Dr. Pirngadi General Hospital in Medan. This is a quantitative study with a cross-sectional design and purposive sampling technique. The research sample consisted of all coronary heart disease patients who sought treatment at the cardiology clinic of Dr. Pirngadi General Hospital in Medan, totaling 50 respondents aged 25-85 years. The results showed that 58% of patients had a high fat intake (>25% of total energy requirements) and 68% had LDL cholesterol levels (≥130 mg/dL). The analysis results showed a relationship between fat intake and LDL cholesterol levels (ρ=0.022; r=0.324). There was a positive and significant but weak correlation between fat intake and LDL cholesterol levels in outpatients with coronary heart disease at Dr. Pirngadi General Hospital in Medan.